2019
DOI: 10.1111/1365-2656.13032
|View full text |Cite
|
Sign up to set email alerts
|

Size‐selective harvesting fosters adaptations in mating behaviour and reproductive allocation, affecting sexual selection in fish

Abstract: The role of sexual selection in the context of harvest‐induced evolution is poorly understood. However, elevated and trait‐selective harvesting of wild populations may change sexually selected traits, which in turn can affect mate choice and reproduction. We experimentally evaluated the potential for fisheries‐induced evolution of mating behaviour and reproductive allocation in fish. We used an experimental system of zebrafish (Danio rerio) lines exposed to large, small or random (i.e. control) size‐selective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
36
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 78 publications
(175 reference statements)
6
36
1
Order By: Relevance
“…When size‐selective fisheries reduce body size variability rapidly and unexpectedly, an individual's ability to discriminate among mates can be suddenly hampered (e.g., Francis & Barber, 2013). Size may become an unreliable indicator of male quality or difficult to evaluate; thus, females may benefit from shifting their attention to other cues (e.g., behavior, courtship display) that are easier to evaluate (de Jong, Amorim, Fonseca, & Heubel, 2018; Sbragaglia et al, 2019). However, other potential traits under sexual selection might correlate with body size, and variability in these traits may be reduced together with size variability.…”
Section: The Effect Of Size‐selective Fisheries On Sexual Selectionmentioning
confidence: 99%
“…When size‐selective fisheries reduce body size variability rapidly and unexpectedly, an individual's ability to discriminate among mates can be suddenly hampered (e.g., Francis & Barber, 2013). Size may become an unreliable indicator of male quality or difficult to evaluate; thus, females may benefit from shifting their attention to other cues (e.g., behavior, courtship display) that are easier to evaluate (de Jong, Amorim, Fonseca, & Heubel, 2018; Sbragaglia et al, 2019). However, other potential traits under sexual selection might correlate with body size, and variability in these traits may be reduced together with size variability.…”
Section: The Effect Of Size‐selective Fisheries On Sexual Selectionmentioning
confidence: 99%
“…At worst, anthropogenic selection can increase the relative frequencies of maladaptive phenotypes decreasing the fitness of harvested populations (Allendorf and Hard 2009;Coltman et al 2003). Experimental studies have shown that responses to human-induced selection can be rapid at both phenotypic, including behavior (Kern et al 2016;Sbragaglia et al 2019;Wong et al 2012) and genetic levels (Bowles et al 2020;Cooke et al 2007;Sutter et al 2012;Uusi-Heikkilä et al 2015). Fisheries-induced selection can occur on traits that explain vulnerability to fishing and on traits that enable the fish to reproduce before becoming captured (Cooke et al 2007;Hollins et al 2018;Redpath et al 2010;Sutter et al 2012;Uusi-Heikkilä et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the size-selection triggered changes in energy allocation patterns, with the large-harvested line investing early and intensively into reproduction, and the small-harvested line investing early but at low intensity into gonad production and more intensively in somatic growth. Moreover, the selection lines differed significantly in their behavioural traits, size variability, allele frequency and gene expression profiles (6,29,34,(40)(41)(42) B. Experimental design.…”
Section: Methodsmentioning
confidence: 99%
“…The zebrafish lines that we studied were subjected to two treatments together with a control: large-harvested line (largest individuals preferentially harvested, the typical case in most fisheries), small-harvested line (smallest individuals preferentially harvested, a possible case in fisheries managed with a maximumsize limit or where dome-shaped selectivity is prevalent) and random-harvested line (control; individuals randomly harvested with respect to size). Previous results revealed substantial changes in life history, size variation, gene expression, allele frequencies as well as individual and collective behavioral traits (6,29,34,(40)(41)(42), but the mechanistic underpinning of the collective behavioral changes observed in the cited studies remained untackled.…”
Section: Introductionmentioning
confidence: 99%